An update of anthropogenic CO2 storage rates in the western South Atlantic basin and the role of Antarctic Bottom Water - Rios, AF; Velo, A; Pardo, PC; Hoppema, M; Perez, FF (2012)
The western basin of the South Atlantic from 10°N to 55°S and from the coast to the Mid-Atlantic Ridge is a region with large uncertainties as to the storage of anthropogenic CO 2 (Cant). Our analysis of data of the last three decades provides a Cant storage rate of 0.92 ± 0.13 mol m − 2 y − 1 , i.e., 13%–35% higher than previous estimates in this area. The low but significant Cant concentrations ([Cant]) in the large volume of relatively well ventilated Antarctic Bottom Water (AABW) may well be the underlying cause of this higher storage rate. In fact, the significant contribution in terms of Cant of this ventilated AABW that enters the western South Atlantic Ocean was calculated to be 0.055 ± 0.02 Pg C y − 1 or 0.20 mol m − 2 y − 1 . Instead of being based on the annual trend, the Cant specific inventory (in mol m − 2 ) evolution is more consistently computed as a function of the atmospheric xCO 2 perturbation in ppm, (0.64 mol m − 2 ppm − 1 ). This methodology allows improved projections of Cant storage rates over long periods.